1991
DOI: 10.1073/pnas.88.6.2451
|View full text |Cite
|
Sign up to set email alerts
|

Genetic organization and diversity of the hepatitis C virus.

Abstract: The nucleotide sequence of the RNA genome of the human hepatitis C virus (HCV) has been determined from overlapping cDNA clones. The sequence (9379 nucleotides) has a single large open reading frme that could encode a viral polyprotein precursor of 3011 amino acids. While there is little overall amino acid and nucleotide sequence homology with other viruses, the 5' HCV nucleotide sequence upstream ofthis large open reading frame has substantial simiarit to the 5' termini of pestiviral genomes. The polyprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
1,021
0
18

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,557 publications
(1,044 citation statements)
references
References 25 publications
5
1,021
0
18
Order By: Relevance
“…The coNS3/4A gene had a sequence homology of 79% with the region at nucleotide positions 3417-5475 of the HCV-1 reference strain. 46 A total of 433 nucleotides differed. On an amino-acid level, the homology with the HCV-1 strain was 98% (15 amino acids differed).…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…The coNS3/4A gene had a sequence homology of 79% with the region at nucleotide positions 3417-5475 of the HCV-1 reference strain. 46 A total of 433 nucleotides differed. On an amino-acid level, the homology with the HCV-1 strain was 98% (15 amino acids differed).…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…To study the biosyncontrol. 1,5,6 The coding region encodes structural proteins in thesis of HCV structural proteins and their pathogenic its N-terminal portion that include a nonglycosylated core role, we constructed transgenic mice, expressing type protein (p22), which associates with genomic RNA to form 1b HCV structural proteins (core, E1, and E2) in liver the nucleocapsid. The C-terminal 20 amino acids of the core tissues.…”
mentioning
confidence: 99%
“…12 30% to 70% of patients Hepatitis C virus (HCV) contains a single 9.4 kb (/)-with hepatitis B virus (HBV)-negative HCC are seropositive stranded RNA genome, containing a single open reading for HCV, which in the United States may represent as many frame that encodes a polyprotein of 3,011 amino acids. 1,2 The as 40% of all cases of HCC. polyprotein is post-translationally processed to yield several Success in controlling HCV infection with antiviral agents mature structural and nonstructural proteins.…”
mentioning
confidence: 99%
“…HCV has a positivestranded RNA as its genome. Nucleotide sequence analyses of HCV clones isolated in different places in the world revealed that there are significant sequence diversities (8)(9)(10)(11)(12)(13)(14)(15). The analysis of the region of non-structure 5 (NS5) of the HCV genome found, at least five different HCV genotypes in the world (16).…”
Section: Introductionmentioning
confidence: 99%